Geometry ability in Senior High School Students: Based on Learning Style - Pipit Firmanti; Yuberta, Fauzi; Dimas Danar Septiadi; Nurulzhia Rahma Nisa (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2024)
Geometry becomes an important component in mathematics which is learned by students at every stage. Learning style is one of the factors that influence students' geometry abilities. Therefore, it is important to describe how students' geometry abilities are viewed from learning styles. This research is quantitative descriptive research. The instruments used were a learning style questionnaire and a van hiele thinking test (VHGT). The data analysis technique used is descriptive statistical techniques with percentages, namely data from geometry tests that are successfully collected and then analyzed using a category assessment scale. The instruments used were the learning style questionnaire and the Van Hiele thinking test (VHGT). The research subjects were 276 high school students from eleven different schools in West Sumatra with the dominant learning style being visual as many as 104 students, followed by auditory as many as 98 and kinesthetic as many as 74. The results showed that the average students' geometric ability was 47.4 (on a scale of 0-100). In addition, students with a visual learning style have a higher average geometric ability compared to other learning styles. Therefore, it is hoped that teachers can consider using learning models that apply the Van Hiele level of thinking and the dominant learning style in geometry classes, for example by integrating technology.